Effect of Adding Synbiotic Isolate Pediococcus Pentosaceus Strain N6 and Cassava Peel Flour on the Digestibility of Dry Matter and Organic Matter of Super Native Chickens - Sukani; N.br Ketaren; S.Mutia R.M (Jurnal Peternakan Integratif, 2023)
Public awareness of healthy food is currently getting stronger. Food should be free from antibiotics. As consequence the use of antibiotics as feed additives should be prohibited because it has the potential to produce residues in livestock products and indirectly impact consumers. An alternative substitute for antibiotics that has been widely developed is the administration of synbiotics. Synbiotics are a combination of probiotics and prebiotics. The purpose of this study is to investigate Pediococcus pentosaceus strain N6 isolate as a probiotic and cassava peel as a prebiotic. The research design used was a non-factorial Completely Randomized Design (CRD) with 4 treatments and 5 replications. Each replication consisted of 5 chickens with treatments; P0: Basal ration without additive feed (control), P1: Basal ration + additive feed 150 ml/kg ration, P2: Basal ration + additive feed 300 ml/kg ration and P3: Basal ration + additive feed 450 ml/kg ration. The best digestibility of dry matter and organic matter of super native chicken was obtained in treatment the addition of feed additives of 450 ml/kg ration. In conclusion feed additives of 450 ml/kg ration give good effect on digestibility as well as on feed consumption, dry matter consumption and organic matter consumption